Chemical characteristics of flakes from arrowroot starch (Maranta arundinacea L.) and soybean flour (Glycine max L.) with variation of ginger extract (Zingiber officinale) : Karakteristik kimia flakes pati garut (Maranta arundinacea L.) dan tepung kedelai (Glycine max L.) dengan variasi penambahan ekstrak jahe emprit (Zingiber officinale) - Endang Safitri; Nanik Suhartatik; Vivi Nuraini (Fakultas Sains dan Teknologi Unisri, 2025)
Flakes are flat shaped ready-to-eat food and usually served by adding milk for the breakfast menu as alternatif besides rice. Flakes usually made from high-carbohydrate foods such as corn, rice and wheat. In This study, the flakes used arrowroot starch, soybean flour and emprit ginger extract. The purpose of this study was to determine the formulation of arrowroot starch and soybean flour with the addition of ginger extract. Arrowroot and the soybean flour were source of protein and fiber. Flake were design to have higher protein and fiber. This study used Completely Randomized Design (CRD) consisting of two factors, the first factor was the ratio of arrowroot starch and soybean flour (90:10 , 85:15 , 80:20). The second factor was the percentage of ginger extract (10, 15, and 20%). The results of study showed that the ratio of arrowroot starch and soybean flour 80:20 with the addition 15% ginger extract was the best flakes formulation. The flake contain 2.62% moisture, 1.73% of ash, 7.53% of fat, 9.58% protein, 9.62% crude fiber, 78,55% carbohydrate. The organoleptic (triangle) test reported that 11 panelists stated that there was a ginger taste in the flakes and 9 panelists stated that the flakes having ginger like aroma. Using arrowroot and soybean flour could improve the nutrition properties of the flakes. Consuming flake with high protein was important to support days.